PENGARUH PENERBITAN SUKUK TERHADAP REAKSI PASAR (SURVEY TERHADAP PERUSAHAAN-PERUSAHAAN YANG MENERBITKAN OBLIGASI SYARIAH YANG TERDAFTAR DIBURSA EFEK INDONESIA SELAMA TAHUN 2015) - Iskandar, Mulya; Ridwan, Ridwan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aims to determine how the influence of a sukuk instrument issuance on market reactions listed on the Indonesia Stock Exchange (IDX) during 2015. The research method used in this study is quantitative research. Quantitative research contains a relationship between cause and effect. The type of data used is secondary data, data collection used by the author is to know the relationship between two or more variables. The object to be examined in this study is the total value and rating of the issuance of Islamic bonds (sukuk) companies as independent variables and cumulative abnormal return shares of companies that issue Islamic bonds (sukuk) listed on the Indonesia Stock Exchange in 2015. The results of this study indicate the value of sukuk bond issuance and sukuk bond issuance ratings jointly affect stock returns. The value of issuing sukuk bonds partially affects stock returns and the rating of bond issuance has an effect on return.